(untitled) (University of Khartoum Engineering Journal, 2022)
This paper investigates the influence of vertical loads on laterally loaded piles. It includes laboratorymodel tests of steel piles embedded in medium stiff clay and a parametric study. The laboratory tests wereperformed at the Faculty of Engineering, University of Khartoum in Sudan. The parametric study considers theeffects of different values of the vertical load and the length–to-diameter (L/d) ratio of the pile on the pilebehavior. The performance of pile considered will include the ultimate lateral capacity of pile, the pile headdeflection, load-maximum moment curves and the shear force along the length of the pile.